2022
DOI: 10.1007/s10734-022-00876-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of brokers in cultivating an inter-institutional community around open educational resources in higher education

Abstract: Brokers are individuals who facilitate transfer of knowledge and resources, and coordinate efforts across boundaries of organizations. They are defined by their role rather than their organizational position. Brokers might be imperative for the formation and maintenance of inter-institutional relationship as they have the responsibility and the necessary structural position to connect otherwise separate groups. In the context of this study, brokers had the role to cultivate an inter-institutional community aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Their findings indicated that a deliberate strategy is needed with a dual focus on a supportive learning space for teachers to have discussions, generate ideas and to experiment with open textbooks, and on the role of facilitators to organize structured meetings and to connect teachers' needs with information and expertise within the institute. In line with this, Baas et al (2022a) showed the importance of brokers in cultivating an inter-institutional community on OER. Due to their personal, small-scale, and content-oriented approaches, brokers were pivotal in encouraging teachers to engage with the community.…”
Section: Towards Sustainable Oer Communitiessupporting
confidence: 58%
See 1 more Smart Citation
“…Their findings indicated that a deliberate strategy is needed with a dual focus on a supportive learning space for teachers to have discussions, generate ideas and to experiment with open textbooks, and on the role of facilitators to organize structured meetings and to connect teachers' needs with information and expertise within the institute. In line with this, Baas et al (2022a) showed the importance of brokers in cultivating an inter-institutional community on OER. Due to their personal, small-scale, and content-oriented approaches, brokers were pivotal in encouraging teachers to engage with the community.…”
Section: Towards Sustainable Oer Communitiessupporting
confidence: 58%
“…OER communities might facilitate boundary crossing across institutes (Baas et al, 2022a). Findings on applied and realized value denote that it became easier for teachers to connect with peers, and to initiate collaboration projects across institutes, because boundaries between institutes had diminished.…”
Section: Teachers' Perceived Value: What's In It For Mementioning
confidence: 99%
“…For instance, SCRELE effectively coordinated activities for the advisors who worked with policy makers of MoE in the macrosystem to give a seminar on the 2017 Standards, coming in contact with the writing group in the microsystem. By and large, these agents played similar roles as brokers who facilitated boundary crossing and sustainable collaboration among communities or institutions (Baas et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We had a conversation and then she put me in touch with D, Mosaic The connection between E and C was crucial to everything that followed in our partnership. E, a known, well-networked and trusted contributor among minoritized groups within the discourse of environmental equity, acted as a significant 'cultural broker' (Baas et al, 2023) The Walking the Walk project would not have been possible if we had not made connections with external partners through a combination of 'structured' (Palinkas et al, 2015) and 'snowball' sampling (Parker et al, 2019) The degree to which connections were maintained in person and through cooperative working were key distinguishing features between Walking the Walk and Landscape Stories. Walking the Walk involved connections between university staff and three minoritized community walking groups.…”
Section: Connectednessmentioning
confidence: 99%